NK cells and human pregnancy--an inflammatory view. - Sargent, I; Borzychowski, A; Redman, C (2006)
For several years, reproductive immunology has been dominated by the 'Th1/Th2' hypothesis, in which the fetus avoids maternal T-cell rejection through a bias towards T-helper (Th)2 cytokine production. The discovery that normal pregnancy is a controlled state of inflammation, at an early stage at the implantation site and also later systemically, has challenged this concept, as has the finding that the predominant immune interactions in the decidua are between the placental trophoblast and maternal natural killer (NK) cells instead of T cells. Here, we extend this concept to the interaction between the trophoblast and NK cells in the maternal circulation. We suggest novel ways in which the trophoblast might stimulate the maternal systemic inflammatory response, and how dysfunctional NK-cell activation could result in the maternal syndrome of pre-eclampsia.